Lie-algebraic structure of (2 + 1)-dimensional Lax-type integrable nonlinear dynamical systems - Prykarpatsky, A.K.; Hentosh, O.Ye. (Український математичний журнал, 2004)
A Hamiltonian representation for a hierarchy of Lax-type equations on a dual space to the Lie algebra of integro-differential operators with matrix coefficients extended by evolutions for eigenfunctions and adjoint eigenfunctions of the corresponding spectral problems is obtained via some special Båcklund transformation. The connection of this hierarchy with Lax-integrable two-metrizable systems is studied. Знайдено гамільтопове зображення для ієрархії рівнянь типу Лакса на спряженому просторі алгебри Лі інтегро-диференціальних операторів із матричними коефіцієнтами, розширеної еволюцією власних функцій відповідних спектральних задач, за допомогою деякого спеціального перетворення Беклунда. Досліджено зв'язок цієї ієрархії з інтегровними за Лаксом двометризованими системами.